IMPLEMENTASI PELAYANAN KESEHATAN BAGI PESERTA/PASIEN BPJS KESEHATAN DI RUMAH SAKIT PRIMA KOTA PEKANBARU - Hutasoit, Sion Einar Edlyn; Indra, Mexsasai; Junaidi, Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The establishment of the Social Security Agency on Health is a part of NationalHealth Insurance which is a government policy in the health sector that aims to ensure theprovision of adequate health care facilities for the entire community asparticipants/patients. In Pekanbaru, one of the advanced referral health facilities that hascollaborated with Social Security Agency on Health Pekanbaru is Prima HospitalPekanbaru since 2017. The results of research related to health services organized at PrimaHospital Pekanbaru, there are problems found in the field, especially for Social SecurityAgency on Health participants/patients. The purpose of the research is to find out how theimplementation; inhibiting factors; and efforts made in improving health services for SocialSecurity Agency on Health participants/patients at Prima Hospital Pekanbaru. The authoruses sociological research methods in analyzing the implementation of health services forSocial Security Agency on Health participants/patients at Prima Hospital Pekanbaru.The implementation of health services for BPJS Health participants/patients atPrima Hospital Pekanbaru City is quite good, but on the other hand it has not been able toreach the level of participant/patient satisfaction. The inhibiting factors are influenced bymiscommunication and the public's lack of understanding of BPJS Health procedures andarrangements at Prima Hospital Pekanbaru City as well as the imbalance in the number ofBPJS Health participants/patients with the number of health workers. Efforts to improvehealth services for BPJS Health participants/patients at Prima Hospital Pekanbaru Citystart from accommodating every participant/patient complaint which has been managedwith the presence of the Prima Hospital PIPP Team and then work assessment standardswill be implemented.Keywords: Social Security Agency on Health Pekanbaru – Participants/Patients –Prima Hospital Pekanbaru